2014
DOI: 10.1111/jace.12787
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Grain Boundary Mobility in Undoped and Doped Alumina

Abstract: The grain boundary mobility of polycrystalline alumina (α‐Al2O3), and the effective grain boundary mobility of the basal (0001) plane as it grew into polycrystalline alumina, was determined for undoped alumina, alumina doped with 23 ppm MgO, and alumina doped with 13 ppm CaO at 1600°C. Doping with MgO at a level below the solubility limit decreased the grain‐boundary mobility from 2.7 × 10−15 to 1.5 × 10−15 m2/s, and doping with CaO at a level below the solubility limit increased the mobility to 3.5 × 10−15 m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…This variation in diffusivity is small considering the relatively large variation in impurities between samples made from different source powders and tested by different groups. 26 Al grain-boundary diffusion in Y 2 O 3 -doped alumina is consistent with reported values for Cr 3+ chemical tracer measurements in similar undoped and Y 2 O 3 -doped materials. However, the results have been rationalized in the context of aliovalent charge compensating impurities that tend to balance one another in the undoped samples.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…This variation in diffusivity is small considering the relatively large variation in impurities between samples made from different source powders and tested by different groups. 26 Al grain-boundary diffusion in Y 2 O 3 -doped alumina is consistent with reported values for Cr 3+ chemical tracer measurements in similar undoped and Y 2 O 3 -doped materials. However, the results have been rationalized in the context of aliovalent charge compensating impurities that tend to balance one another in the undoped samples.…”
Section: Introductionsupporting
confidence: 90%
“…Those values are only slightly lower than our Cr 2 O 3 chemical tracer values and are reasonably consistent with values measured indirectly from permeability studies, 20 when extrapolated to higher temperatures. 5,26 The experimental results 27 provide new insights into how average Al 2 O 3 grain-boundary diffusivity is affected by aliovalent dopants. The reproducibility is unanticipated given Al 2 O 3 's reputation as an impurity sensitive highly extrinsic material and the fact that the samples were prepared from powders of different purity, in different labs, and tested using different methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in this geometry have been used for more than three decades in measuring growth rate anisotropy in ceramics, e.g. Alumina [22][23][24][25][26][27][28][29], Barium titanate [30][31][32][33] and Strontium titanate [34][35][36]. In some of these previous experiments and in this paper, measurements of the mean migration distance of different single crystal orientations into the polycrystalline matrix and of the matrix grain size as a function of time, temperature, and single crystal surface orientation are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ca ions could contaminate the green body and thus cause abnormal grain growth (especially in the case of alumina). Akiva et al demonstrated that the grain boundary mobility of alumina doped with 13 ppm CaO increased in comparison to the undoped alumina. The morphology of CaO‐doped polycrystalline alumina was plate‐like.…”
Section: Introductionmentioning
confidence: 99%